Pyomyositis in an adult with diabetes mellitus - Enrique Otoya, Enrique Otoya (2021)
A 63-year-old male patient, diabetic and on insulin treatment, with pain and increased volume at the level of the left anterior hemithorax, with ultrasound and tomography study compatible with collection at the level of the pectoralis major muscle. In the puncture a purulent and fetid material was obtained, confirming the diagnosis of pyomyositis. Streptococcus constellatus was isolated in pus culture.With poor response to initial medical treatment, it required surgical drainage and broad antibiotic coverage.